Composite Materials Characteristic Analysis of Marble Waste And Resin With Bending Test - Ihsan Ihsan Ihsan; Nuzuli Fitriadi (Jurnal Inotera, 2018)
Marble is a natural rock product that is widely used in daily life. There is a lot of marble powder as a by-product during the production process. This powder can be converted into valuable items. To transform this by-product to be economically valuable items, there is a way to propagate composite products from marble powder and resin. There are four composite mixing ratios carried out in this research, namely 50/50%, 40/60%, 30/70%, and 20/80%. The mixing composites test shows bending strength and elasticity of the composite material.